Y = -3x - 1......so we sub in -3x - 1 in for y in the other equation
2x + 5y = 12
2x + 5(-3x - 1) = 12....now distribute the 5 through the parenthesis
2x - 15x - 5 = 12...add 5 to both sides
2x - 15x = 12 + 5..combine like terms
-13x = 17...divide both sides by -13
x = -17/13
now sub in -17/13 for x in the other equation
y = -3x - 1
y = -3(-17/13) - 1
y = 51/13 - 1
y = 51/13 - 13/13
y = 38/13
so the solution is (-17/13, 38/13)
k-1/2b=47 because the difference is subtraction and half b is a half fraction and it equals 47.
Answer:
Find the interval of convergence of the following series
Possible Answers:
(4,6)
[4,6)
(4,6)
[4,6]
Correct answer:
(4,6)
Explanation:
Step-by-step explanation:
Find the interval of convergence of the following series
Possible Answers:
(4,6)
[4,6)
(4,6)
[4,6]
Correct answer:
(4,6)
Explanation:
Answer:
Step-by-step explanation:
We want to find the equation of a circle with a center at (7, 2) and a point on the circle at (2, 5).
First, recall that the equation of a circle is given by:
Where (<em>h, k</em>) is the center and <em>r</em> is the radius.
Since our center is at (7, 2), <em>h</em> = 7 and <em>k</em> = 2. Substitute:
Next, the since a point on the circle is (2, 5), <em>y</em> = 5 when <em>x</em> = 2. Substitute:
Solve for <em>r: </em>
<em /><em />
Simplify. Thus:
Finally, add:
We don't need to take the square root of both sides, as we will have the square it again anyways.
Therefore, our equation is: